Effects of empagliflozin on metabolic parameters in polycystic ovary syndrome: A randomized controlled study. (2nd April 2019) - Javed, Zeeshan; Papageorgiou, Maria; Deshmukh, Harshal; Rigby, Alan S.; Qamar, Unaiza; Abbas, Jehangir; Khan, Amer Y.; Kilpatrick, Eric S.; Atkin, Stephen L.; Sathyapalan, Thozhukat
Summary: Background: Empagliflozin is a sodium‐glucose‐cotransporter‐2 inhibitor that improves cardiovascular risk and promotes weight loss in patients with type‐2 diabetes. Polycystic ovary syndrome (PCOS) is associated with obesity and increased cardiovascular risk; therefore, empagliflozin may be of benefit for these women. The aim of this study was to compare the effects of empagliflozin vs metformin on anthropometric and body composition, hormonal and metabolic parameters in women with PCOS. Materials and methods: A randomized open‐label study was conducted in women with PCOS who were randomized to either empagliflozin 25 mg (n = 19) or metformin 1500 mg (n = 20) daily for 12 weeks. The main outcomes assessed were changes in anthropometric and body composition, hormonal and metabolic parameters. Results: Univariate analysis showed significant differences in weight (empagliflozin: −1.4 ± 3.2% vs metformin: 1.2 ± 2.3%; P = 0.006), body mass index (empagliflozin: −1.4 ± 3.2% vs metformin: 1.1 ± 2.2%; P = 0.006), waist circumference (empagliflozin: −1.6 ± 2.8% vs metformin: 0.2 ± 2.1%; P = 0.029) and hip circumference (empagliflozin: −2.0 ± 3.0% vs metformin: 1.1 ± 1.9%; P = 0.001), basal metabolic rate (empagliflozin: −1.8 ± 2.9% vs metformin: 0.1 ± 1.9%, P = 0.024) and fat mass (empagliflozin: −0.7 ± 4.9% vs metformin, 3.2 ± 5.0%; P = 0.023) between the empagliflozin and the metformin groups. These differences were confirmed in linear regression analysis after adjustment for relevant covariates. There were no significant changes in hormonal or metabolic parameters between both groups. Conclusion: There was a significant improvement in anthropometric parameters and body composition, in overweight and obese women with PCOS after 12 weeks of treatment with empagliflozin compared to metformin, although no changes were seen in hormonal or metabolic parameters.